2013
DOI: 10.3747/pdi.2012.00018
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Nutritional Risk Index as a Prognostic Factor in Peritoneal Dialysis Patients

Abstract: ♦ Background: The Geriatric Nutritional Risk Index (GNRI) might be a useful screening tool for malnutrition in dialysis patients. However, data concerning the GNRI as a prognostic factor in peritoneal dialysis (PD) patients are scarce. ♦ Methods: We reviewed the medical records at Yeungnam University Hospital in Korea to identify all adults (>18 years) who received PD; 486 patients were enrolled in the study. ♦ Results: The initial low, middle, and high GNRI tertiles included 162, 166, and 158 patients respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 21 publications
4
58
0
1
Order By: Relevance
“…In older patients with sepsis, a GNRI of 82-87 and a GNRI <82 could independently predict the mortality risk [21]. In peritoneal dialysis patients, a low initial GNRI tertile was associated with mortality [10]. In our present study, the multivariate analysis demonstrated that the GNRI was an independent significant factor predicting postoperative respiratory complications.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In older patients with sepsis, a GNRI of 82-87 and a GNRI <82 could independently predict the mortality risk [21]. In peritoneal dialysis patients, a low initial GNRI tertile was associated with mortality [10]. In our present study, the multivariate analysis demonstrated that the GNRI was an independent significant factor predicting postoperative respiratory complications.…”
Section: Discussionmentioning
confidence: 49%
“…However, despite its frequent use, albuminemia remains an unreliable indicator of the nutritional status, because it may be more closely related to inflammation or the hydration status than to malnutrition. Recently, the Geriatric Nutritional Risk Index (GNRI), a new prognostic index of nutritional status-related complications, has been proposed for the evaluation of at-risk elderly patients [1,2,3,4,5,6] and hemodialysis patients [7,8,9,10,11,12], and it was revealed to be a predictor of morbidity and mortality and for the possible use in grading the patient's nutritional status. The relationship between the GNRI and the morbidity of patients with gastrointestinal cancer has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they also found that lowmiddle GNRI have the highest mortality rate (HR 4.28, 95%CI 2.66 to 6.88) if patients with low phosphorus level [38]. The association between GNRI and mortality has been further validated from PD and nondialysis CKD patients [39,40]. Based on all the available studies, our meta-analysis further confirmed the results that high GNRI score can decrease the risk of all-cause mortality, while low GNRI was associated with high mortality for dialysis patients.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies showed the usefulness of the GNRI as a new marker for malnutrition screening in dialysis patients [12,13]. A few reports have also shown that in PD patients, the GNRI is associated with nutritional status and is an independent risk factor for mortality [14,15]. Therefore, we believe that any differences in GNRI status in relation to PA in PD patients also require elucidation.…”
mentioning
confidence: 94%